Structure–activity relationship studies of non-carboxylic acid peroxisome proliferator-activated receptor α/δ (PPARα/δ) dual agonists. Issue 21 (1st November 2016) - Okazaki, Shogo; Shioi, Ryuta; Noguchi-Yachide, Tomomi; Ishikawa, Minoru; Makishima, Makoto; Hashimoto, Yuichi; Yamaguchi, Takao
Graphical abstract: Abstract: The peroxisome proliferator-activated receptors (PPARs) are ligand-dependent transcription factors that contribute to the regulation of lipid, glucose and cholesterol homeostases. They are considered as therapeutic targets for metabolic diseases such as dyslipidemia and type 2 diabetes mellitus. Various PPAR agonists have been developed, but most of them contain a carboxylic acid (CA) or thiazolidinedione (TZD) moiety, which is essential for the activity. However, we recently discovered non-CA/non-TZD class PPARα/δ dual agonists having an acetamide structure. Here, we describe structure–activity relationship (SAR) studies of these novel acetamide-based PPARα/δ dual agonists. The SAR studies revealed that the acetamide functionality and adjacent methyl group contribute greatly to the agonistic activity. Compound( S )-10 was the most potent PPARα/δ dual agonist among the compounds synthesized (PPARα EC50  = 17 nM, PPARδ EC50  = 23 nM).